Establish operating conditions for optimal output characteristics in reactivity controlled combustion engine - Sinnappadass Muniyappan; Ravi Krishnaiah (Scientific Reports)
Abstract This work aims to determine the optimal engine operating conditions for balanced combustion, performance and emissions characteristics with considerable reduction in smoke and nitrogen oxides (NOx). This work examined direct injected (DI) 30% mahua biodiesel-diesel as high reactive fuel (HRF) and port fuel injected (PFI) ethanol as low reactive fuel (LRF) in reactivity controlled compression ignition (RCCI) combustion at different engine loads and ethanol energy shares (EES) (0, 10, 15, 20, 25, and 30%). The RCCI engine was able to access low temperature combustion (LTC) with improved brake thermal efficiency (BTE), lower smoke and NOx with a trade-off in carbon monoxide (CO) and hydrocarbon (HC). The duty conditions of modern engines require single optimal operating condition to suit applications such as hybrid powertrain, generators and irrigation pumps. Using response surface methodology (RSM) it was established that 28.43% EES at 83.4% engine load resulted in optimal output responses for their due weightages assigned. This was validated by experimental results. In RCCI mode BTE of 32.54%, brake specific energy consumption (BSEC) of 10.79 MJ/kWh were realized. Also, smoke and NOx were reduced by 34.8% and 29.3%, with a compromise in CO and HC increase by 36.4% and 34.9% compared to DI mode. All the engine output parameters reported were within acceptable range. HC and CO can be mitigated with conventional catalytic convertors.